DAMPAK PANDEMI COVID-19 TERHADAP TRANSISI TENAGA KERJA SEKTOR FORMAL - Clara Tridiana; Erwin Tanur (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
This research aims to analyze the different impacts of the pandemic on skilled and unskilled workers on the job transition in the labor market focused on the formal sector. The transition in this research is the move from the formal to the informal sector or unemployment. Apart from the pandemic, other independent variables are education and tenure as individual characteristics, GRDP, and the unemployment rate as characteristics of the labor market. This research uses Sakernas data from August 2021 with a total sample of 30,000 Census Blocks. The probit model is used to determine the pandemic's effect on moving the formal sector (skilled and unskilled workers). Based on the regression of the probit, it is known that the impact of the pandemic on skilled workers is higher than that of unskilled ones to change jobs from the formal sector. The pandemic has had a positive and significant impact on the work transition in the formal sector.